The lessons of developed countries for Covid-19 exit strategies - Svetličič, Marjan (Teorija in praksa, 2020)
The objective of the article was to establish whether the strategies of today's developed countries (DCs) can today be applied to crisis-exit strategies, including the Covid-19 pandemic. DCs have in their transition to higher development levels generally relied on protectionist policies in the areas of trade, patents and foreign direct investment until reaching the top, when they kicked away the ladder of protectionism and started to hypocritically propagate liberalism. Such experiences are also useful for less developed countries so long as the international context provides them with adequate policy space and they use crises as opportunities and react on time. The pandemic could be a good starting point for structural changes in the system of international (economic) relations if the mind-sets and the system that created all of these crises are changed
Keywords: Covid-19; Crises; Develpment politics; ekonomski nacionalizem; Epidemics; Epidemije; izhodne strategije; Krize; nova ureditev; pravice intelektualne lastnine; razvite dežele; Razvojna politika; razvojne strategije; tuje neposredne investicije